Misclassification of Patients with Spinocerebellar Ataxia as Having Psychogenic Postural Instability Based on Computerized Dynamic Posturography - Herdman, Susan J.; Hall, Courtney D.; Eggers, Rachael; Sampson, Stasha; Goodier, Sydne; Filson, Becky (Frontiers in Neurology, 2011)
Specific criteria have been developed based on computerized dynamic posturography (CDP) to assist clinicians in identifying patients with psychogenic balance problems1-4. Patients with known Spinocerebellar Ataxia (SCA) meet several of the criteria for psychogenic balance problem and risk being misclassified as having imbalance of psychogenic origin. However, our research shows that patients with SCA may be distinguished from patients with psychogenic balance problems in several ways. We compared test performance on CDP and the observation of specific behaviors that are associated with psychogenic balance problems in patients with SCA (n = 43) and patients with known psychogenic balance problems (n = 40). Chi square analysis was used to determine if there were significant differences between the groups for the frequency of each criterion for psychogenic CDP and Observed Behaviors. Level of significance was Bonferroni corrected for multiple comparisons. Sensitivity, specificity, and positive likelihood ratios were calculated for each criterion. Hierarchical cluster analysis was used to examine whether the two patient groups demonstrated similar groupings of criteria. Comparison of the results of these analyses identified two criteria that were significantly more frequent in the Psychogenic group than in the SCA group: Regular Periodicity of sway and Circular Sway. Sensitivity, specificity and positive likelihood ratios identified two additional criteria, Inconsistent Motor Responses and Large lateral Sway that also seem to suggest a psychogenic component to a person’s imbalance. Prospective studies are needed to validate the usefulness of these findings.